Campylobacter pylori Detection in Gastric Mucosa: Association with Gastritis - Alain Paradis; Marie Gourdeau; Suzanne Lambert; Sylvain Lavoie; Suzanne Lemire; Claude Parent; Réjean Cantin (Canadian Journal of Gastroenterology)
ln order to evaluate the association between Camphlobacter pylori and gastritis, two biopsies were taken from the duodenal bulb, antrum, body and fundus (and from lesions if there were any) in 100 consecutive patients referred to this gastroscopic clinic For each site, one biopsy was for histology and C pylon detection by Warthin-Starry staining, and the second biopsy was for culture. In addition, for each patient a gastric brushing was Gram stained. Twenty-one patients were excluded from the study. Among the remaining, 13 patients had positive biopsy culture for C pylori and, of these, 30 (91%) had gastritis (including 23 with active chronic gastritis). This culture sensitivity increased with the number of biopsies. Forty-two patients had a positive brushing specimen, of which 30 (71%) had gastritis. Gram stain on a brushing specimen had a sensitivity of 84.8%, in comparison with the biopsy culture. Of the 23 patients with positive Warthin-Starry stain , 19(83%) had an histology of gastritis. There was a strong correlation between the presence of C pylori in the stomach mucosa and the gastritis. The incidence of C pylori associated gastritis is similar in Quebec to other parts of the world. The biopsy culture is a simple and specific test, and at least two biopsies are necessary for a good sensitivity. Gram stain on a brushing specimen is an adequate test for rapid detection of C pylori in the stomach.